2016
DOI: 10.15212/fmch.2016.0115
|View full text |Cite
|
Sign up to set email alerts
|

How well are families doing? A description of family well-being in South Africa

Abstract: Objective:The purpose of this study was to describe the well-being of a sample of families from low socioeconomic communities in the Western Cape South Africa in terms of family resilience, family satisfaction, parenting styles, family structure and family functioning.Methods: The study used a descriptive survey design and sampled 358 adult family members. Results:The results indicate that although family functioning is challenged, parents are perceived to be using an authoritative parenting style and having a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Further evidence from Sub-Saharan Africa suggests independent associations between paternal orphaning and parental absence and children experiencing sexual violence, with girls being at higher risk of sexual abuse [45]. In South Africa, a study conducted in the Western Cape found that family satisfaction ranked lower among households with absent fathers, partly due to limited economic resources [46]. It is also possible that in the present study the divorce and separation captured in the ACEs retrospective report occurred before two years of age and hence the association between divorce/separation as an ACE and absent fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence from Sub-Saharan Africa suggests independent associations between paternal orphaning and parental absence and children experiencing sexual violence, with girls being at higher risk of sexual abuse [45]. In South Africa, a study conducted in the Western Cape found that family satisfaction ranked lower among households with absent fathers, partly due to limited economic resources [46]. It is also possible that in the present study the divorce and separation captured in the ACEs retrospective report occurred before two years of age and hence the association between divorce/separation as an ACE and absent fathers.…”
Section: Discussionmentioning
confidence: 99%
“…An exhaustive search for peer-reviewed journal articles with 'resilience' (or 'resilient' or 'resiliency') in the title or abstract, written by South African social workers over the two years from 2015 to 2016, turned up 12 publications, with three authors appearing more than once: Fouché, Truter and Van Breda (Dolbin-Macnab, Jarrott, Moore, O'hora, De Chavonnes Vrugt & Erasmus., 2016;Dykes, 2016;Goliath & Pretorius, 2016;Kasiram & Beattie, 2015;Raniga & Mthembu, 2016;Roman, Serena Ann, Charl & Xin-Cheng, 2016;Soji, Pretorius & Bak, 2015;Truter & Fouché, 2015;Truter, Fouché & Theron, 2016;Van Breda, 2015b;Van Breda, 2016c;Van Breda, 2016a). This suggests a small but growing interest in resilience research among social workers in South Africa, with topics including families, adolescents, youth-headed households, care-leavers, student and qualified social workers, aging caregivers, organisations, drug abuse, HIV and poverty.…”
Section: Introductionmentioning
confidence: 99%
“…These findings concur with those of Isaacs et al (2018), who adapted and validated the Family Resilience Assessment Scale in an Afrikaans rural community in South Africa and found communication to be the underlying component of all domains of family resilience. In addition, Roman et al (2016) found communication to be a strong predictor of family adaptation since it enhances problem-solving abilities during a family crisis. In line with these findings, Lewis (2018) argues that consistent parenting with clear communication serves as a protective factor for children across cultures, mainly because it nurtures and creates a responsive environment.…”
Section: Discussionmentioning
confidence: 97%